An Epidemiological Study of Suffocation Deaths In Twin Cities of South India - Maddileti, Gandla Bala; Mohanty, Sujan Kumar; Kumar, Virendra; Reddy, K Bhaskar; Bhuvan, V; Yamini , K (Journal of Indian Academy of Forensic Medicine, 2015)
In spite of advancement in medical facilities, the end of life is inevitable. Suffocation deaths have increased over the years and are becoming a large group in medico legal autopsies. In such deaths, a detailed and meticulous autopsy plays a major role to solve the case, while the scene visit and collection of samples have their own significance. To analyse the recent trends such as manner, methods, motive etc., in suffocation deaths, a prospective study was conducted for two years period. 34 suffocation deaths were studied, which comprised 0.18% of all Forensic autopsies; 38.23% of the cases were aged between 21-30 years. Males constituted 67.63% of all the cases. The most frequent method of suffocation death was smothering (35.29%) followed by environmental and traumatic asphyxia (20.58%), choking (17.64%) and positional asphyxia (5.88%). The most common manner of suffocation was found to be accidental (67.64%). But in homicidal cases (29%), the common motive was domestic disputes. Only 30% of suffocation victims were found positive for blood alcohol.